2020
DOI: 10.1101/gr.259655.119
|View full text |Cite
|
Sign up to set email alerts
|

Dual threshold optimization and network inference reveal convergent evidence from TF binding locations and TF perturbation responses

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 70 publications
(92 reference statements)
8
49
0
Order By: Relevance
“…S8). Thus, the strength and location of the binding signal are meaningful predictors of whether significantly bound genes will respond to the perturbation, consistent with our earlier findings (Kang et al 2020). [-200, -100] bin.…”
Section: In Yeast Cells Tf Binding Locations and Strengths Discriminsupporting
confidence: 90%
See 1 more Smart Citation
“…S8). Thus, the strength and location of the binding signal are meaningful predictors of whether significantly bound genes will respond to the perturbation, consistent with our earlier findings (Kang et al 2020). [-200, -100] bin.…”
Section: In Yeast Cells Tf Binding Locations and Strengths Discriminsupporting
confidence: 90%
“…Data on where in the genome each TF binds were expected to be of great value in determining its targets, but multiple studies have shown that, in the available large ChIP-chip and ChIP-seq datasets, the genes in whose regulatory DNA a TF binds do not correspond well to those that respond to perturbation of the TF (Gitter et al 2009;Lenstra and Holstege 2012;Cusanovich et al 2014;Kang et al 2020). We followed up on these observations by training machine learning models to predict which genes would respond to perturbation of a TF, given data on the TF's binding locations and several features reflecting the gene's epigenetic context.…”
Section: Discussionmentioning
confidence: 99%
“…We can broadly categorize timecourses at a dataset level based on existing knowledge. While strong acute regulation events are frequently associated with the direct binding of the induced TF (Kang et al, 2020), over 75% of genes responding in our dataset are new regulatory connections (Appendix Fig S10). Additionally, we find that 79% of genes reported as being directly bound by a TF based on published ChIP measurements do not exhibit a significant expression response in the corresponding TF's induction experiment (Appendix Fig S10; Teixeira et al, 2018).…”
Section: Transcriptional Responses Vary In Amplitude Kinetics and Smentioning
confidence: 99%
“…The final measurement (the gene expression profile) is the asymptotic readout of many layers of regulation and unobserved (but potentially relevant) molecular interactions. Using methods like ChIP-seq or ChIP-exo provides another strategy for determining GRNs that focus on transcription factors (TFs) and their target genes (Harbison et al, 2004;Gerstein et al, 2010;Nègre et al, 2011;Kheradpour & Kellis, 2014;Kim et al, 2014;Kang et al, 2020). Target genes with similar ChIP profiles can exhibit opposite expression responses (Lickwar et al, 2012), and highly expressed portions of the genome can exhibit strong ChIP signal even among unrelated proteins (Teytelman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate improvements coming from better network maps. One likely source of better maps is new, more accurate methods for measuring TF binding locations (53,(75)(76)(77)(78). The input network could also be improved by obtaining TF perturbation data from cells grown in new conditions.…”
Section: Discussionmentioning
confidence: 99%